Earnings differentials between immigrants and natives: The role of occupational attainment - Carlo Dell Aringa; Claudio Lucifora; Laura Pagani (IZA Journal of Migration, 2015)
This paper brings new evidence to the existing literature on earnings differentials and returns to human capital for immigrants and natives. It is the first paper analysing this topic using data drawn from the Italian Labour Force Survey, a large nationally representative dataset. We show that returns to human capital are considerably lower for immigrants as compared to natives and that there is no return to pre-immigration work experience, suggesting imperfect transferability of human capital. In the second part of the paper we explore models of occupational attainment among immigrants and the native born. Our findings suggest that, contrary to what is observed for natives, immigrants' human capital does not contribute to getting access to high-paying occupations.
Keywords: J31; J24; J61; F22; 330; Immigration; Earnings; Returns to human capital; Occupation